Effect of crude palm oil (CPO) as an alternative additive to the binder in asphalt mixture - Mohamad Khaidier, Mohd Raffi (2017)
Warm mix asphalt (WMA) produced in the lower temperature than Hot-mix asphalt (HMA) to reduce the temperature of asphalt for purpose of energy costs can be saved. The production temperatures for warm-mix asphalt are normally around 130°C to 150°C. The objective of this research paper presents a study potential of addition Crude Palm Oil (CPO) as additive to asphalt pavement mix. A total of asphaltic concrete mix designs with 0.5% addition of CPO were prepared in accordance with the JKR Specification. The gradations used are AC 14 to determine the control optimum asphalt content. The mixing and compaction temperatures were selected at 120,130,140°C. During mixing, the determined optimum asphalt content which is 5% and 0.5% of CPO of OAC added into asphaltic concrete mix. All the mix samples were based on the Marshall Mix Design Method. In this study, the volumetric properties such as voids in Total Mix (VTM), voids filled with Asphalt (VFA), bulk density (Gmb) and voids in mineral aggregates (VMA) were investigated. In this study, addition of Crude Palm Oil (CPO) content is an alternative to the conventional asphalt as it can be produced at lower temperatures of about l20°C.